Level of Employee Loyalty from Generation Z - Vincent Vincent; Iventura Fitra Uli Tamba (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Since generation Z dominates North Sumatra province and Medan City has the largest number of residents in North Sumatra province, we want to find out the level of employee loyalty from generation Z Medan City. The data was taken primarily and was distributed to 385 respondents of employees from generation Z Medan City using nonprobability sampling techniques. Data is processed using technical descriptive statistical analysis. The results showed that there are still many employees of Generation Z Medan City who have never changed jobs (44.94%) and the most working period is 1 year - 3 years (41.56%). The level of employee loyalty from generation Z Medan City is in a high category class from the aspects of obedience and submission, responsibility, devotion, and honesty. This is likely influenced by the characteristics of generation Z, the increasing unemployment rate in North Sumatra Province, and the impact of the COVID-19 pandemic. Generation Z women employees are more loyal than men employees, which may be caused by job stability or labor chaos.